Adoption and Scaling Interventions are progressively guided by gender-responsive research methods across CGIAR CRPs, including WHEAT - CGIAR Research Program on Wheat (2020)
Since 2018, researchers and colleagues from within and outside of CGIAR centers have applied gender-responsive research methods in an attempt to unravel the complex social landscapes of different agricultural settings around the world. In doing so, scientists have assessed the dynamics of gender norms, power relations, labor-use, and processes for decision-making in access to and control of resources. These assessments guide research on how social dynamics influence decisions in adoption of climate-smart, energy-saving and cost-effective agricultural technologies.